Adiabatic response of 𝟑𝒔𝟐 → 𝟐𝒑𝟒 and 𝟑𝒔𝟑 → 𝟐𝒑𝟓 neon transitions to laser field variations - Delibašić-Marković Hristina S.; Petrović Violeta M.; Petrović Ivan D. (Kragujevac Journal of Science)
In this research, we delve into the ionization dynamics of neon, focusing on the transitions 3𝑠2 → 2𝑝4 and 3𝑠3 → 2𝑝5. Employing the Landau-Dykhne approximation, we elucidate how variations in laser intensity, atomic charge, and wavelength influence the ionization rates. Our study unveils a detailed dependency of the ionization process on these laser parameters, affirming the laser's pivotal role in atomic excitations. We discover that while the ionization rates are markedly affected by laser intensity and atomic charge, wavelength variations also significantly alter the transition dynamics. This work emphasizes the minimal impact of relativistic effects in neon, thereby establishing it as an excellent system for examining laser-atom interaction nuances. Our findings provide valuable insights into the quantum mechanical underpinnings of laser-induced ionization, enhancing the theoretical framework and informing future experimental inquiries into such interactions.